Age bias in the time of Coronavirus: Implications for research and practice - Iles, Lucinda; Parker, Sharon (CAMBRIDGE UNIV PRESS, 2021)
In their focal article, Rudolph etal. (2021) recognized the aging workforce as a key topic relevant to the pandemic for both researchers and practitioners alike, describing a framework of differential susceptibility and differential impact based on life-span perspectives of aging. We agree that aging workers are of primary importance for psychologists in the pandemic. However, we propose that the differential susceptibility and impact framework can also usefully be considered from a social psychology and age diversity perspective. We argue that the pandemic does not only affect the aging workforce due to natural developmental processes or increased physical susceptibility to illness, but rather, the pandemic exacerbates existing attitudes and biases toward older workers in age-diverse teams and organizations, which can lead to a more hostile work environment for older workers, diminishing team effectiveness, and limiting older workers’ access to work opportunities.